Learning experiences from a time-geographic approach—commodity chains, globalization, everyday life, and sustainability in context. Issue 4 (2nd October 2019) - Westermark, Åsa; Jansund, Bodil
ABSTRACT: There are many approaches to teaching about globalization, commodity chains, and sustainability. Education for sustainable development demands teaching approaches that capture multidimensional and integrated aspects of environmental, social, economic, and political factors. In geography, additional aspects require attention, such as understanding how peoples' everyday lives, living conditions, and business relations depend on contextual circumstances including place, time, and scales. This article presents a time-geographic teaching approach that enables systems thinking through contextual analysis. We present a time-geographically inspired educational approach which was implemented at a Swedish university in a yearly course, from 2007 to 2015 (9 years in total). Next, we review 48 student exam papers regarding how students performed a time-geographic contextual analysis of commodity chains and sustainability. We found that the teaching approach encouraged multiple descriptions and reflections by students. It developed students' abilities to apply geographic concepts and to identify complex relationships in time and space that define sustainability challenges and strategies. Students linked everyday life to global and local processes.